Le meilleur monde est-il un dieu ? Leibniz et Bayle face à l’objection de Diroys - Paul Rateau (Etudes Epistémè)
In paragraphs 197 to 203 of the Essays on Theodicy, Gottfried Wilhelm Leibniz examines, after Pierre Bayle, the objection formulated by the Catholic theologian François Diroys against the thesis that God should always make the best and the most perfect. According to Diroys, it would follow that God, having to create all things as good and perfect as possible, could only produce other gods. The aim of this article is to study the arguments put forward by the three authors – Diroys, Bayle, Leibniz – by showing that they are part of wider controversies, serve distinct purposes (apologetic, sceptical, demonstrative), and are based on different conceptions of freedom and of what is best. The aim is also to highlight, by means of this confrontation, the originality of Leibniz’s thesis of the best of all possible worlds, the particular relationship that it establishes between the whole and the parts (of the universe), its compatibility with the existence of evil, the change and progress that it makes possible. Hence, the best world is not God himself, nor filled with other gods, but the combination of creatures – imperfect and finite in themselves – that satisfies the divine purpose in the most convenient way.